Prevalence of classical swine fever in Karnataka, India - Choori, Prakash (Vet World, 2015)
AIM: The present study was conducted to know the current scenario of classical swine fever (CSF) in Bengaluru Urban, Bengaluru Rural, Chikkaballapur, Madikeri, Mandya, Bagalkot, Gadag, Yadgir, Koppal, and Bidar districts of Karnataka with the using of both antigen and antibody ELISA. MATERIALS AND METHODS: We collected 218 sera and 121 blood samples from pigs from 10 different districts of Karnataka. Screening of sera for CSF IgG antibody and whole blood for CSF virus antigen were carried out using the CSF virus (CSFV) antibody and antigen ELISA kits, respectively. RESULTS: The mean seroprevalence was 41% (89/218) and prevalence of CSFV antigen in blood samples was 32% (39/121) for the 10 districts of Karnataka. Seroprevalence of 61%, 29%, 20%, and 21%; and antigen prevalence of 40%, 50%, 13%, and 12% were recorded for Bangalore, Mysore, Belgaum, and Gulbarga divisions of Karnataka, respectively. CONCLUSIONS: The study revealed an alarmingly high prevalence of CSF, both for the antigen (32%) and antibody (41%) in Karnataka. Southern Karnataka has the highest seroprevalence (61% in Bangalore and 29% in Mysore divisions), which confirms the endemicity of the disease in that region. This could be attributed to the intensive pig farming practices in the region as compared to Northern Karnataka (Seroprevalence of 20% in Belgaum and 21% in Gulbarga divisions), where the commercial pig farming is still in infantile stages.